Інформаційні технології моніторингу рекреаційних дигресій лісів Західного Полісся - Мокрий, В.І. (Екологічна безпека та природокористування, 2012)
Solved the problem of finding, identifying and prospective study of environmental indicators to assess the impact of recreation alpressure on the state of forest ecosystems. A proposed methodology forprofile-chart analysis of satellite imagery, which includes of many factorial the reconnaissance measurements and radiometric analysis of satellite imagery that provides high efficiency of large-scale studies of recreation transformations forests of Western Polesie.